Education about complementary and alternative medicine in cancer self-help groups by trained peers - Joachim Weis; Martina Jablotschkin; Markus Horneber; Diana Steinmann; Claudia M. Witt; Stefanie Helmer; Hans Helge Bartsch (BMC, 2024)
Abstract Purpose On average, about 50% of cancer patients use complementary and alternative medicine (CAM) in addition to conventional cancer treatment. Since there is a high need for information, patients often search for information about CAM and share experiences with peers, especially in self-help groups. In this study, we tested and evaluated an educational concept developed for group leaders of cancer self-help groups on how to approach the topic of CAM in their peer groups. Methods The educational concept has been developed and piloted with health care professionals and representatives from different self-help organizations in Germany. It aims to inform and discuss the possibilities and limitations of CAM in terms of scientific evidence, to reflect user behavior, and to provide a guide on how to find and evaluate reliable and evidence-based information sources. First, self-help group leaders took part in an on-site training where they were educated on various CAM topics with the goal of being able to conduct the educational concept in their respective self-help groups. Then, the educated group leaders performed this concept in their groups. The educational concept was evaluated by both the group leaders and participants with respect to acceptance, usefulness, and satisfaction using paper-pencil questionnaires. The study was conducted in Germany based on an observational study design with a six-month follow-up. For the analyses, descriptive and univariate statistics for dependent samples were used. Results A total of n = 50 interested group leaders conducted the educational program in their groups. The most common implementation barriers were organizational or structural problems, as well as the feeling of being overwhelmed with managing the program in their groups. A total of n = 423 participants were educated with this program by their respective group leaders. The majority felt satisfied with the educational program and improved their knowledge about CAM. At the six months follow-up (T2), significantly more participants had consulted their physicians to inform themselves about CAM and felt more confident in finding reliable information about CAM. Conclusions In this observational study, we have managed to successfully implement an educational concept with respect to the topic of CAM in cancer self-help groups. Based on the results, the concept approach will be modified to include both a CAM- professional and group leader to train the self-help groups. In the future, the effects of the program should be tested by a randomized trial.